MODEL PENGEMBANGAN PROGRAM WIRAUSAHA BARU BERKELANJUTAN SEKTOR PERTANIAN DI KOTA TASIKMALAYA - Muflihah, Ulfah; Heryadi, D Yadi; Widi, Riantin Hikmah (Adbispreneur, 2023)
The New Entrepreneurship Program (WUB) will be implemented over a period of five years (2018-2022) at the Tasikmalaya City regional apparatus covering various fields including the agricultural sector. The success of the WUB program can determine the sustainability of the program. The purpose of this research is: (1) to determine the success of the new agricultural sector entrepreneur program in Tasikmalaya City, (2) to analyze the factors that influence the success and sustainability of the agricultural sector new entrepreneur program in Tasikmalaya City, and (3) formulate a development model for sustainable new entrepreneur program agriculture sector in Tasikmalaya City. This research method uses a survey method. The method used to analyze the success rate of the WUB program in the agricultural sector is the average score on the dimensions of program success, factor analysis of measurement models, and structural models using the SEM Warp-PLS model. This shows the success rate of the agricultural sector WUB program in Tasikmalaya City as a whole the dimensions are 82.48% including the successful category. The characteristics of the actors and supporting institutions influenced the success and sustainability of the WUB program. The success of the WUB program is a mediating variable for the influence of supporting institutions on the sustainability of the WUB program. The model for developing a sustainable new entrepreneurial program for the agricultural sector in Tasikmalaya City can be realized in a synergistic penta helix model. Program Wirausaha Baru (WUB) dilaksanakan dalam kurun lima tahun (2018-2022) pada perangkat daerah Kota Tasikmalaya meliputi berbagai bidang termasuk sektor pertanian. Keberhasilan program WUB dapat menentukan keberlanjutan program tersebut. Penelitian ini bertujuan untuk (1) mengetahui keberhasilan program wirausaha baru sektor pertanian di Kota Tasikmalaya, (2) menganalisis faktor-faktor yang memengaruhi keberhasilan dan keberlanjutan program wirausaha baru sektor pertanian di Kota Tasikmalaya, dan (3) merumuskan model pengembangan program wirausaha baru berkelanjutan sektor pertanian di Kota Tasikmalaya. Metode penelitian ini menggunakan metode survei. Metode yang digunakan untuk mengetahui tingkat keberhasilan program WUB sektor pertanian dengan metode rata-rata skor pada dimensi keberhasilan program, analisis faktor model pengukuran dan model struktural menggunakan permodelan SEM Warp-PLS. Hasil penelitian menunjukkan tingkat keberhasilan program WUB sektor pertanian di Kota Tasikmalaya secara keseluruhan dimensi sebesar 82,48% termasuk kategori berhasil. Karakteristik pelaku dan kelembagaan pendukung berpengaruh terhadap keberhasilan dan keberlanjutan program WUB. Keberhasilan program WUB merupakan variabel mediasi pengaruh kelembagaan pendukung terhadap keberlanjutan program WUB. Model pengembangan program wirausaha baru berkelanjutan sektor pertanian di Kota Tasikmalaya dapat diwujudkan dalam model penta helix secara sinergis.